Perancangan Alat Pemanas Air Tenaga Surya Dengan Metode Kansei Engineering - Hanafi, Imam; Hariyanto, Krisnadi (Journal of System Engineering and Technological Innovation, 2022)
The need for warm water for baths, both for household scale and hospitality scale is very important. During this time the need is met with hot water heated with a furnace or heating using electricity. One alternative to meet the needs of hot water is to use solar media as a supply of energy. The method used in this research is the kansei method. This kansei method is applied to identify consumer desires (Voice of Consumen). This Voice of Consumer is obtained by distributing questionnaires. The distribution of questionnaires is conducted to determine the level of consumer interest of a product, so that SMEs need to have tool / machine water heater is more modern to improve the production, while the questionnaire using scale scale measurement, Lingkert scale used to measure attitudes, opinions, perceptions, a group of people about social phenomena.